2018
DOI: 10.1097/pec.0000000000000754
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Using Pediatrics Emergency Services and Triage Evaluation

Abstract: Most children who were seen in PED were priority 3 and therefore needed to be seen. However, a considerable percentage of priority 4 and 5 could have been seen in ambulatory clinics. Most lower priorities were Saudi nationals who were most likely to leave without being seen. Prolonged LOS, overcrowding, and high percentage of admission are the main challenges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…The admission rates reported in this study after the triage course correlate well with some of the pooled admission rates calculated after a multicenter study that included twelve Canadian Pediatric Emergency Departments [13]. The pooled rates reported by them were 61%, 30%, 10%, 2% and 0.9% for levels 1 – 5, respectively which especially agrees with our results for the lower triage levels [1], [3], [9], whilst triage levels 1 and 2 were within anticipated CTAS level admission rates of 70 – 90%, 40 – 70%, 20 – 40%, 10 – 20% and 0 – 10% respectively [10]. This contrasts with the admission rates reported according to the patient encounter sheets before the triage course, which emphasised the beneficial effect of the training the PEM staff received.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The admission rates reported in this study after the triage course correlate well with some of the pooled admission rates calculated after a multicenter study that included twelve Canadian Pediatric Emergency Departments [13]. The pooled rates reported by them were 61%, 30%, 10%, 2% and 0.9% for levels 1 – 5, respectively which especially agrees with our results for the lower triage levels [1], [3], [9], whilst triage levels 1 and 2 were within anticipated CTAS level admission rates of 70 – 90%, 40 – 70%, 20 – 40%, 10 – 20% and 0 – 10% respectively [10]. This contrasts with the admission rates reported according to the patient encounter sheets before the triage course, which emphasised the beneficial effect of the training the PEM staff received.…”
Section: Discussionsupporting
confidence: 90%
“…Our patients’ characteristics were found to follow a normal distribution curve, which is expected. We found a mean age of 5.5 years, although El-Desoky et al, [9] who performed a study in a nearby hospital and found that the toddler age group had the highest number of patients. A possible explanation for this is the fact that our hospital had many sickle cell patients making up approximately 20% of our pediatric population (according to an internal census).…”
Section: Discussionmentioning
confidence: 53%
“…[9][10][11][12][13] In the wake of a global pandemic, as institutions continue to endure increased stress on existing healthcare and staffing resources, experience-driven efforts should primarily focus on these metrics. 16,17 We did find univariate associations between ESI scores and KPI, an association that was lost in the multivariate model. It is likely that this association is lost because of the inherent interaction between ESI and time to provider and total length of stay.…”
Section: Discussionmentioning
confidence: 75%
“… 9 13 In the wake of a global pandemic, as institutions continue to endure increased stress on existing healthcare and staffing resources, experience-driven efforts should primarily focus on these metrics. 16 , 17 …”
Section: Discussionmentioning
confidence: 99%
“… 17 , 24 Two more studies, one conducted in Qatar and the other in Negara, assessed length of stay, the adverse impacts on patient outcome, and their associations with a highly crowded ED, revealing that the major reason for increased length of stay at an ED was overcrowding. 18 , 25 …”
Section: Discussionmentioning
confidence: 99%